Trade Unions, Workers and the Protection of Workers’ Rights: A Vicious Circle with No Escape? - Saveski, Zdravko (Identities: Journal for Politics, Gender and Culture, 2015)
The overall problem with the trade unions, workers and protection of the workers’ rights is that the workers wait for the trade unions to defend them, protect them and advance their rights, while the trade unions can not achieve that without the workers’ support. Without their support, not being able to realistically threaten with a sanction, the trade union representatives go to negotiate with the owners with an empty gun, showing weakness that is simply not enough in order to successfully defend and advance workers’ rights. Precisely this inefficiency of the trade unions is a reason enough for the workers to continue distrusting the trade unions. That is how the vicious circle is created.In this analysis we look at the trade unions, then at the workers, we will locate the issues, and in the final part we will offer certain ideas on how to overcome the problem. Actually, the offering of suggested solutions itself is what differentiates the counterproductive pessimistic approach from the pessimistic approach which criticizes in order to improve. Author(s): Zdravko Saveski Title (English): Trade Unions, Workers and the Protection of Workers’ Rights: A Vicious Circle with No Escape? Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 100-113 Page Count: 14 Citation (English): Zdravko Saveski, “Trade Unions, Workers and the Protection of Workers’ Rights: A Vicious Circle with No Escape?,” Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015): 100-113.